2016
DOI: 10.1093/nar/gkw1079
|View full text |Cite
|
Sign up to set email alerts
|

dbDEMC 2.0: updated database of differentially expressed miRNAs in human cancers

Abstract: MicroRNAs (miRNAs) are often deregulated in cancer and are thought to play an important role in cancer development. Large amount of differentially expressed miRNAs have been identified in various cancers by using high-throughput methods. It is therefore quite important to make a comprehensive collection of these miRNAs and to decipher their roles in oncogenesis and tumor progression. In 2010, we presented the first release of dbDEMC, representing a database for collection of differentially expressed miRNAs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
210
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(214 citation statements)
references
References 38 publications
4
210
0
Order By: Relevance
“…The prediction results were verified by another two databases dbDEMC 52 and miR2Disease, 53 both of which record experimentally verified disease-related miRNAs. Our prediction results showed that 10 of the top 10 and 49 of the top 50 candidate miRNAs were verified to be associated with BN by at least one of the two databases.…”
Section: Case Studymentioning
confidence: 73%
“…The prediction results were verified by another two databases dbDEMC 52 and miR2Disease, 53 both of which record experimentally verified disease-related miRNAs. Our prediction results showed that 10 of the top 10 and 49 of the top 50 candidate miRNAs were verified to be associated with BN by at least one of the two databases.…”
Section: Case Studymentioning
confidence: 73%
“…Specifically, we selected 16 common diseases among the four databases (i.e. dbDEMC[39], miR2Disease[40], miRwayDB[41] and PhenomiR[42]) for the subsequent case studies and validated the prediction results across all the databases. The 16 common diseases are Breast Neoplasms, Cervical Intraepithelial Neoplasia, Colorectal Neoplasms, Hepatocellular Carcinoma, Lymphoma, Lung Neoplasms, Leukemia, Nasopharyngeal Neoplasms, Liver Neoplasms, Ovarian Neoplasms, Pancreatic Neoplasms, Prostatic Neoplasms, Stomach Neoplasms, Thyroid Neoplasms, Urinary Bladder Neoplasms and Uterine Cervical Neoplasms.…”
Section: Resultsmentioning
confidence: 99%
“…While approximately 300 miRNAs have demonstrated a role in carcinogenesis, more than 2000 miRNAs have been found differentially expressed in human cancers (Yang et al, 2017) and evidence that different types of cancer can be discriminated by miRNA profiling has been reported (Iorio & Croce, 2017;Petrovic, Ergün, & Isenovic, 2017). In cutaneous melanoma, there is increasing evidence for a significant role of specific miRNAs as oncogenes or tumour suppressor genes (Mione & Bosserhoff, 2015;Mirzaei et al, 2016;Varamo, Occelli, Vivenza, Merlano, & Lo Nigro, 2017) as well as their involvement in other aspects of melanoma biology (Leibowitz-Amit, Sidi, & Avni, 2012;Luo, Weber, Osen, Bosserhoff, & Eichmuller, 2014;Sun, Zhou, Majid, Kashani-Sabet, & Dar, 2014;Voller, Ott, & Bosserhoff, 2013).…”
Section: G Ener Al Fe Ature S Of Mirna Smentioning
confidence: 99%